Expression differences in mitochondrial and secretory chaperonin 60 (Cpn60) in pancreatic acinar cells - Li, Y. (Cell Stress Society International, 2003)
In pancreatic acinar cells, chaperonin Cpn60 is present in all the cellular compartments involved in protein secretion as well as in mitochondria. To better understand the role Cpn60 plays in pancreatic secretion, we have evaluated its changes under experimental conditions known to alter pancreatic secretion. Quantitative protein A–gold immunocytochemistry was used to reveal Cpn60 in pancreatic acinar cells. Cpn60 immunolabelings in cellular compartments involved in secretion were found to decrease in acute pancreatitis as well as upon stimulation of secretion and in starvation conditions. A major increase in Cpn60 was recorded in diabetic condition. This was normalized by insulin treatment. Although in certain situations changes in secretory enzymes and in Cpn60 correlate well, in others, nonparallel secretion seemed to take place. In contrast, expression of mitochondrial Cpn60 in acinar cells appeared to remain stable in all conditions except starvation, where its levels decreased. Expression of Cpn60 in the secretory pathway and in mitochondria thus appears to behave differently, and Cpn60 in the secretory pathway must be important for quality control and integrity of secretion.